The impact of foreign aid on economic rural development in Zimbabwe: case of lower Gweru. - Ziko, Praise I. (Midlands State University, 2019)
One of the most important and longstanding arguments in development literature is whether foreign aid promotes economic growth in recipient countries especially rural areas and it adds to the growing literature of foreign aid. Foreign aid aims to improve economic conditions and quality of life in developing countries. The literature on the efficacy of foreign aid to date has been inconclusive due to its debatable nature as to whether it promotes development or it aids to the destruction of economies. The aim of the study was to examine whether aid is essential for the growth of developing countries or it is a deceitful measure that is used to cripple economies of African countries. The research adopted qualitative data gathering technique through prearranged interviews and focus group discussion which is aimed at giving detailed explanation of information within their real life context. 12 respondents from the focus group discussion and the interviews managed to participate giving a synopsis of the impact of foreign aid to rural economic development in their communities. Findings indicated that aid is ineffective at promoting development using the comparison of three case studies across the globes which are Tanzania, Malawi and Pakistan to strengthen and obtain drastic results. The findings in the case studies showed that aid has got little or no effect on the development of developing countries due to the corruption of the elite governments in receiving countries so that they stay in power and the motives of donor countries to pursue the self interests of their countries. The study pointed out the advantages and disadvantages of foreign aid showing that Zimbabwe suffers from aid volatility, aid dependency and to mention just a few. The researcher managed to point out some recommendations for the government and policy makers after the findings to take into consideration which could be considered as helpful for the growth and development of the nation. Some of the recommendations are as follows: the government should utilize foreign aid in developmental activities to boost the economy; the conditions related with foreign aid should be clear and easy to implement and beneficial to both parties, the native people should be included in planning meetings for best results, the government must genuinely provide aid to its communities without manipulation and to mention a few.